2022
DOI: 10.2478/fcds-2022-0011
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Green Supply Chain Transportation System for an Automotive Company Based On Bi-Objective Optimization

Abstract: Recently, due to the increasing awareness of communities regarding environmental issues and environmental regulations, companies have evolved to provide products with lower prices and better quality to retain and attract customers. Economics should also pay attention to environmental goals. Therefore, it is essential to provide a supply chain model that can consider both economic and environmental objectives. In this paper, the green direct supply chain network is presented to an automotive company, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…It is found that adding these indicators to the model can effectively reduce supply chain costs [43]. Based on economic and environmental goals in the supply chain model, another study built a supply chain that includes transportation cost, carbon emissions, industrial productivity and transportation time [44]. By considering the above research content and the actual application environment of the existing supply chain, the supply chain index in Table 3 For small and medium-sized manufacturing enterprises with transit, the network optimization problem of green supply chain can be defined as the random order quantity of customers.…”
Section: A Construction Of Enterprise Greensupplychainand Preliminary...mentioning
confidence: 99%
“…It is found that adding these indicators to the model can effectively reduce supply chain costs [43]. Based on economic and environmental goals in the supply chain model, another study built a supply chain that includes transportation cost, carbon emissions, industrial productivity and transportation time [44]. By considering the above research content and the actual application environment of the existing supply chain, the supply chain index in Table 3 For small and medium-sized manufacturing enterprises with transit, the network optimization problem of green supply chain can be defined as the random order quantity of customers.…”
Section: A Construction Of Enterprise Greensupplychainand Preliminary...mentioning
confidence: 99%
“…6. A bi-objective optimization model was suggested by Syah et al [10] in order to configure an efficient transportation system within an automotive company.…”
Section: Published Researchmentioning
confidence: 99%